A Model of Nano-Processing Methods to Remove Heavy Elements from Soil Samples from the City of Shatrah - Kadhim, Ibtihaj Ahmed; Kadhim, Zainab J; Mohammed, Azhar Saeed (American Journal of Biodiversity, 2025)
Background: A field A study was carried out to determine the levels of some harmful substances in samples of some areas of the city of Shatrah, which are different in terms of their residential, commercial and industrial nature. Methodology: Some strategies approved by scientific centers were implemented, such as grinding, heating and digesting the samples, then sending them to measure the concentrations of the elements with an atomic spectrometer, and then comparing them with the values specified by the World Health Organization and research centers. Results: We noticed that the elements of lead and cadmium were higher than the permissible limits in most of the study models, and the industrial city recorded the highest results, which were (165, 1.6, and 34) ppm , respectively (lead, cadmium, copper). This is due to the fact that the area is industrial and has many blacksmith shops, painting and lubrication workshops, in addition to the movement of cars and the high smoke from exhausts supported by lead compounds, in addition to the smoke transmitted from the neighboring areas from the factories that manufacture plaster, marble and ceramics, and the desertification of the are from trees. We recommend using some nano -solutions that can be used by planting some plants that absorb elements (sunflower and Indian mustard) or if possible replacing the soil or washing it and adding lime or phosphate or compost or using microbes that fix metals.